The Concept Of Evil And Its Truth In View Of Philosophical Buildings And The Words Of Reason - Ali Hassan, Arkan (Opción, 2019)
Speech scientists have been studying the issue of evils and related issues in two subjects of the doctrines of Muslims, the first subject of monotheism un- der the title of monotheism in the moral, the Almighty said ((God is the creator of everything)) (2). The second topic is the divine justice, that Almighty does not do ugly and does not leave Hassan (3), and many philosophers have felt the seriousness of the situation even counted a key focus in all philosophical discussions (4). Socrates was of the view that good is the origin of man and evil emergency. Galen believes that some people are good in their natures and some are evil. Others believe that it contains two aspects of good and evil (Cav- laton). And some of them look at the pessimistic view of the human view that man is evil by nature (as Freud). But many researchers believe that human nature is not good or evil, education and the environment are the basis in determining the characteristic of one of them (5). The world that these intel- lectuals portrayed is a world full of evil, sadness and sorrow, While the world depicted by our speakers and philosophers is a world full of hope, beautiful and wonderful (6).